Factors influencing the quality of nursing care in an intensive care unit in Saudi Arabia - Alalyani, Mesheil M. (Curtin University, 2011)
Quality care in intensive care units is expected by patients and is mandatory for nurses and other health professionals to provide. In Saudi Arabia, the demand for intensive care units (ICUs) is growing rapidly, partly due to the high levels of road trauma and a population increase. In response to these issues, the government has increased the number of ICU beds in some public tertiary regional hospitals. A corresponding increase in patients and a shortage of specialized nurses has major implications for nurses’ ability to provide quality care. In the Western world there is comprehensive literature related to research and factors that influence nursing care. To date, however, no such study has been conducted in an ICU in Saudi Arabia. The purpose of this study was, therefore, to explore and describe factors that influence nursing care in a Saudi Arabian ICU. Additionally, since clinical governance has been described as a structured system for promoting quality care and health service planning, a further aim was to describe the findings within this framework.This study employed a single exploratory descriptive case study using a qualitative approach. Data were collected from various sources with thematic analysis being used to establish themes that emerged from the data. The proposition taken in this case study was that multiple factors influence the quality care registered nurses provide in an ICU setting. It was an assumption that these factors would be both internal and external to the ICU. Findings from this study concurred with this assumption uncovering multiple, complex and interrelated factors that influenced the quality of nursing care in the ICU. It also uncovered factors which were located in the conduit between the internal and external environment: namely intermediate factors. The environment was seen as: direct factors that immediately affected nurses and their ability to provide quality care; intermediate factors were those that encapsulated regular, but intermittent elements; and indirect factors related to elements external to the ICU. Within each of these categories themes and sub-themes emerged. Themes in the direct factors were Continuance: with sub themes of Shift work arrangement, Workload, Collegiality, and Unit management. Burden of responsibility: with sub themes of Educational preparation and Availability of Resources. Proximity: emerged as a theme which related to being close contact with patients.Themes in the intermediate factors were: Relationships with superiors, as well as Policies and protocols. Themes in the indirect factors were: Leadership and bureaucracy, Quality management, and Ongoing education. Together these factors had a profound influence on the quality of nursing care in the ICU. Some had distinctive characteristics whilst others overlapped and were interrelated clarifying and explaining aspects of the complex open system in which nursing care was provided. It is anticipated that these findings will not only have relevance to the ICU in the setting, but also to other hospitals in the Saudi Arabian health care system.